A RETROSPECTIVE ANALYSIS ASSESSING THE FREQUENCY OF PATIENTS WILLING TO UNDERGO RETREATMENT OF ORTHODONTIC TREATMENT AFTER RELAPSE - Antony, Monica; Mary Varghese, Remmiya; L. , Leelavathi (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Orthodontic relapse is the tendency for teeth to return to their pre-treatment position. It is difficult for the tooth to be maintained in the corrected position that was achieved by orthodontic treatment without proper retention. Factors that cause the teeth to move back to original malocclusion include periodontal, gingival, occlusal, and growth-related factors. The aim of the study is to assess the frequency of patients willing to undergo retreatment of orthodontic treatment after relapse.Materials and methods: 588 data points were collected on the study population between June 2010 and April 2020 that had removable orthodontic treatment done due to relapse. The data was imported to the software IBM SPSS Version 23.0 and analyzed using descriptive statistics and Pearson's correlation. Graphs were obtained, and the results were tabulated. Statistical significance was set at